2007
DOI: 10.1002/anie.200701089
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Cellular Multilayers with Nanometer‐Sized Extracellular Matrix Films

Abstract: Tissues and organs consist of a complex organization of cells, extracellular matrix (ECM), and signaling molecules. In particular, blood vessels and skin are a highly organized hierarchical layer composed of various types of cells and ECM layers. The construction in vitro of three-dimensional (3D) cell-polymeric material composites has created notable advances in tissue regeneration.[1] However, an effective methodology to fabricate a 3D multilayer composed of cells and an ECM layer with the appropriate compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
165
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 193 publications
(167 citation statements)
references
References 18 publications
2
165
0
Order By: Relevance
“…12 We focused on cell adhesive properties of ECM-surrounding cell microenvironment. In general in vitro cell culture method, we obtain only cellular monolayers probably due to absence of sufficient ECM on cell surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…12 We focused on cell adhesive properties of ECM-surrounding cell microenvironment. In general in vitro cell culture method, we obtain only cellular monolayers probably due to absence of sufficient ECM on cell surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In this flow experiment for the LbL process in the microfluidic channel, the values of Q, a, and b at the narrowest region were 0.35 mL/min, 4 mm, and 1 mm, respectively. The mechanical force at 100g that was applied to the cells by centrifugation [ρ × (4/3) × 3.14 × r 3 × 100 × g] was calculated using a cell density (ρ) of 1.05 g/cm 3 , a spherical cell radius (r) of 10 μm, and g of 9.8 N/Kg. 15 The mechanical force (0.4 mdyn) that was applied to a cell by centrifugation under these experimental conditions was higher than the force that was applied to a cell by FSS (0.02 × 3.14 × r 2 = 0.15 μdyn).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has demonstrated that gelatin adhesion on the fibronectin (FN) layer was necessary for thickness enhancement of the FN layer. 3 A cellular multilayer was not fabricated by only one coat. 25 Cell adhesion onto cells at a lower layer may be related to the thickness of the BFN layer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations